Aspek prosodi dalam berbahasa penutur bukan Melayu (Jurnal Bahasa, 2007)
This study dis cusses how the prosody aspect of Chinese speakers affects their learning process of Malay language. In this study, the sound system and word structure of Chinese language were identified and compared with the structure of Malay language word syllables. Chinese language (focusing on Mandarin) is a tonal language; its tone patterns form part of the word structure and function as a distinctive factor in differentiating the meaning of a word. On the other hand, the Malay language is classified as an intonation language which means that no matter how any particular sound was articulated, the literal meaning of the word stays the same. In this study, the initial and.final sounds in the Chinese language were matched with the building of word syllables of Malay language as well as identifying the phonetic realization of its phones. This study analyzed and compared the sound systems and syllable structures in Mandarin and Malay languages using interviews as a primary source of normal conversations to generate graphical representations of intonation that were then compared with the reference intonation (as per Beijing) acquired/ram an interactive Mandarin CD-ROM produced in China. This study shows that the degree of hybridization correlates with the system and structure of Chinese and Malay languages. This, in turn, suggests that when there are similarities in the articulation of sounds for both languages, the learning process becomes easier.